What do Long-Term Satellite Data Reveal about Forest Dynamics in the Paphos Forest? - Theocharidis, Christos; Eliades, Marinos; Gitas, Ioannis; Papoutsa, Christiana; Kontoes, Haris; Christofe, Andreas; Danezis, Chris; Hadjimitsis, Diofantos G. (My University, 2024)
This study examines the long-term dynamics of the Paphos forest in Cyprus using Landsat satellite data for Vegetation Indices (VIs), MODIS data for evapotranspiration, and CHIRPS data for precipitation from 1991 to 2022. Sen's slope method was applied to analyse the trends in the data, revealing statistically significant positive trends in the vegetation indices despite the nearly constant precipitation, indicating increased forest vegetation over the past 30 years. Scatterplots were created mainly to examine correlations within the VIs and precipitation data but with low R-squared values ranging between 0.15-0.44. The study outcomes highlight a complex relationship with evapotranspiration and a weak correlation between precipitation and vegetation indices. These findings could be essential in understanding how forests work, especially in a semi-arid environment like Cyprus.
Keywords: Time series analysis; Satellites; Correlation; Time series analysis; Vegetation mapping; Landsat; Forestry